Brain Tumours and Inflammatory Markers: Mini-Review - Michelle Hui, Ling Tiong; Wan Azman, Wan Norlina; Mat Zin, Anani Aila; Idris, Zamzuri; Maulidiani, M.; Mat Desa, Wan Nur Syuhaila (IIUM Medical Journal Malaysia, 2024)
An inflammatory biomarker is an indicating substance that facilitates the process of cell injury and promotes the development of cancer cells. The brain structure naturally protects the extracellular matrix (ECM), which consists of microglia, astrocytes, and neurons, by separating them from harm with the blood–brain barrier (BBB). Yet, the inflammation process damages the brain cells, thus releasing inflammatory markers into the plasma. Chronic inflammation results from persistent inflammation, and any failure of control mechanisms within the brain tissues will promote the development of cancer cells. Previous studies showed that several proinflammatory biomarkers, which included interleukin-6 (IL-6), tumour necrosis factor-α (TNF-α), and C-reactive protein (CRP), were observably higher in patients with glioblastoma compared to those with healthy brain tissues. However, the relationship between proinflammatory factors and glioma development remains unclear. Against such background, this review discusses the potential association between inflammatory markers and a brain tumour, along with the importance of these parameters.